FOXP1 forkhead transcription factor is associated with the pathogenesis of endometrial cancer. Issue 5 (May 2016) - Mizunuma, Makito; Yokoyama, Yoshihito; Futagami, Masayuki; Horie, Kayo; Watanabe, Jun; Mizunuma, Hideki
Abstract: Endometrial cancers are mostly estrogen-dependent. FOXP1 is a P subfamily of forkhead box (FOX), and known as an estrogen-responsive transcription factor. The aims of this study were to examine histological location of FOXP1 in normal and malignant endometrium, and to investigate a possible association between FOXP1 and other factors considered to be involved in pathogenesis of endometrial cancer. The levels of FOXP1, estrogen receptor (ER)α, and ERβ expression were examined immunohistochemically in normal and malignant endometrium obtained from 75 women (8 normal, 8 atypical endometrial hyperplasia, and 59 endometrial cancers from grade 1 to 3). The effects of estrogen on ERα, FOXP1, KRAS, and PTEN expression were analyzed in telomerase-immortalized human endometrial stromal cells (T HESCs) by Western blotting. Western blotting was also used to examine the effect of FOXP1 plasmid DNA or siRNA transfection on KRAS and PTEN expression in Ishikawa cells (well differentiated endometrioid adenocarcinoma), HEC-50B cells (poorly differentiated endometrioid adenocarcinoma), and T HESCs, respectively. FOXP1 was expressed in normal and malignant endometrium, but the rate of expression was different depending upon menstrual cycle and pathological grade of malignancy. FOXP1 expression in nucleus and cytoplasm of grade 3 endometrioid cancers was significantly lower than that of grade 1 and 2 ones. Estradiol increased levels of FOXP1 and KRAS expression in a dose- and time-dependent manner in T HESCs cells, and FOXP1 transfection or knockdown led to increase or decrease of KRAS expression but not PTEN. KRAS expression level was significantly related to FOXP1 and ERα levels in cancer tissues. Estradiol did not affect KRAS expression in T HESCs cells transfected with FOXP1 siRNA. These results suggest that FOXP1 is involved in estrogen dependent endometrial cancers through KRAS pathway.